Fiscal implications from the political crisis in the Republic of North Macedonia - Kostadinoska Miloseska, Snezana; Petkovski, Vladimir (Economic Development, Journal of the Institute of Economics – Skopje, 2019)
In the paper fiscal implication are examined from the perspective of the political crisis1 in the Republic of North Macedonia, which obviously still endures. As consequence of that, the economy is in a state of perpetual decline, among other things, public finances are deteriorating, i.e., there are unfavorable fiscal implications. For this purpose, the paper analyzes in detail the separate implications of public revenues and expenditures, deficits and public debt. Тhe results show a decline, both on the side of public revenues and on the side of public expenditures. The most important thing is that the reduction of public expenditures, especially capital expenditures, is larger part dependent from political crisis. From the analysis made it is perceived that the deficit and the debt in these crisis years were not adequately managed, nor serious structural reforms started, nor with reforms in the management of public finances
Keywords: fiscal implication; public revenues and expenditures; deficits; public debt